Improving the quality of financial management at public universities - Trần Thế Lữ (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Financial management in public universities is an important issue that determines the quality and effectiveness of education, training and university development. This article clarifies the main concepts and proposes solutions to improve the quality of financial management at public universities.